24.2: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-  
|-  
| [https://dlmf.nist.gov/24.2.E1 24.2.E1] || [[Item:Q7398|<math>\frac{t}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullinumberB{n}\frac{t^{n}}{n!}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{t}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullinumberB{n}\frac{t^{n}}{n!}</syntaxhighlight> || <math>|t| < 2\pi</math> || <syntaxhighlight lang=mathematica>(t)/(exp(t)- 1) = sum(bernoulli(n)*((t)^(n))/(factorial(n)), n = 0..infinity)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[t,Exp[t]- 1] == Sum[BernoulliB[n]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Failure || Successful || Successful [Tested: 6] || Successful [Tested: 6]
| [https://dlmf.nist.gov/24.2.E1 24.2.E1] || <math qid="Q7398">\frac{t}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullinumberB{n}\frac{t^{n}}{n!}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{t}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullinumberB{n}\frac{t^{n}}{n!}</syntaxhighlight> || <math>|t| < 2\pi</math> || <syntaxhighlight lang=mathematica>(t)/(exp(t)- 1) = sum(bernoulli(n)*((t)^(n))/(factorial(n)), n = 0..infinity)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[t,Exp[t]- 1] == Sum[BernoulliB[n]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Failure || Successful || Successful [Tested: 6] || Successful [Tested: 6]
|-  
|-  
| [https://dlmf.nist.gov/24.2#Ex1 24.2#Ex1] || [[Item:Q7399|<math>\BernoullinumberB{2n+1} = 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\BernoullinumberB{2n+1} = 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>bernoulli(2*n + 1) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>BernoulliB[2*n + 1] == 0</syntaxhighlight> || Failure || Failure || Successful [Tested: 3] || Successful [Tested: 3]
| [https://dlmf.nist.gov/24.2#Ex1 24.2#Ex1] || <math qid="Q7399">\BernoullinumberB{2n+1} = 0</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\BernoullinumberB{2n+1} = 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>bernoulli(2*n + 1) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>BernoulliB[2*n + 1] == 0</syntaxhighlight> || Failure || Failure || Successful [Tested: 3] || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/24.2#Ex2 24.2#Ex2] || [[Item:Q7400|<math>(-1)^{n+1}\BernoullinumberB{2n} > 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>(-1)^{n+1}\BernoullinumberB{2n} > 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>(- 1)^(n + 1)* bernoulli(2*n) > 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>(- 1)^(n + 1)* BernoulliB[2*n] > 0</syntaxhighlight> || Failure || Failure || Successful [Tested: 1] || Successful [Tested: 3]
| [https://dlmf.nist.gov/24.2#Ex2 24.2#Ex2] || <math qid="Q7400">(-1)^{n+1}\BernoullinumberB{2n} > 0</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>(-1)^{n+1}\BernoullinumberB{2n} > 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>(- 1)^(n + 1)* bernoulli(2*n) > 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>(- 1)^(n + 1)* BernoulliB[2*n] > 0</syntaxhighlight> || Failure || Failure || Successful [Tested: 1] || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/24.2.E3 24.2.E3] || [[Item:Q7401|<math>\frac{te^{xt}}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullipolyB{n}@{x}\frac{t^{n}}{n!}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{te^{xt}}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullipolyB{n}@{x}\frac{t^{n}}{n!}</syntaxhighlight> || <math>|t| < 2\pi</math> || <syntaxhighlight lang=mathematica>(t*exp(x*t))/(exp(t)- 1) = sum(bernoulli(n, x)*((t)^(n))/(factorial(n)), n = 0..infinity)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[t*Exp[x*t],Exp[t]- 1] == Sum[BernoulliB[n, x]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Failure || Successful || Successful [Tested: 18] || Successful [Tested: 18]
| [https://dlmf.nist.gov/24.2.E3 24.2.E3] || <math qid="Q7401">\frac{te^{xt}}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullipolyB{n}@{x}\frac{t^{n}}{n!}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{te^{xt}}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullipolyB{n}@{x}\frac{t^{n}}{n!}</syntaxhighlight> || <math>|t| < 2\pi</math> || <syntaxhighlight lang=mathematica>(t*exp(x*t))/(exp(t)- 1) = sum(bernoulli(n, x)*((t)^(n))/(factorial(n)), n = 0..infinity)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[t*Exp[x*t],Exp[t]- 1] == Sum[BernoulliB[n, x]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Failure || Successful || Successful [Tested: 18] || Successful [Tested: 18]
|-  
|-  
| [https://dlmf.nist.gov/24.2.E4 24.2.E4] || [[Item:Q7402|<math>\BernoullinumberB{n} = \BernoullipolyB{n}@{0}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\BernoullinumberB{n} = \BernoullipolyB{n}@{0}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>bernoulli(n) = bernoulli(n, 0)</syntaxhighlight> || <syntaxhighlight lang=mathematica>BernoulliB[n] == BernoulliB[n, 0]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
| [https://dlmf.nist.gov/24.2.E4 24.2.E4] || <math qid="Q7402">\BernoullinumberB{n} = \BernoullipolyB{n}@{0}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\BernoullinumberB{n} = \BernoullipolyB{n}@{0}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>bernoulli(n) = bernoulli(n, 0)</syntaxhighlight> || <syntaxhighlight lang=mathematica>BernoulliB[n] == BernoulliB[n, 0]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/24.2.E5 24.2.E5] || [[Item:Q7403|<math>\BernoullipolyB{n}@{x} = \sum_{k=0}^{n}{n\choose k}\BernoullinumberB{k}x^{n-k}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\BernoullipolyB{n}@{x} = \sum_{k=0}^{n}{n\choose k}\BernoullinumberB{k}x^{n-k}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>bernoulli(n, x) = sum(binomial(n,k)*bernoulli(k)*(x)^(n - k), k = 0..n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>BernoulliB[n, x] == Sum[Binomial[n,k]*BernoulliB[k]*(x)^(n - k), {k, 0, n}, GenerateConditions->None]</syntaxhighlight> || Failure || Successful || Successful [Tested: 9] || Successful [Tested: 9]
| [https://dlmf.nist.gov/24.2.E5 24.2.E5] || <math qid="Q7403">\BernoullipolyB{n}@{x} = \sum_{k=0}^{n}{n\choose k}\BernoullinumberB{k}x^{n-k}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\BernoullipolyB{n}@{x} = \sum_{k=0}^{n}{n\choose k}\BernoullinumberB{k}x^{n-k}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>bernoulli(n, x) = sum(binomial(n,k)*bernoulli(k)*(x)^(n - k), k = 0..n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>BernoulliB[n, x] == Sum[Binomial[n,k]*BernoulliB[k]*(x)^(n - k), {k, 0, n}, GenerateConditions->None]</syntaxhighlight> || Failure || Successful || Successful [Tested: 9] || Successful [Tested: 9]
|-  
|-  
| [https://dlmf.nist.gov/24.2.E6 24.2.E6] || [[Item:Q7404|<math>\frac{2e^{t}}{e^{2t}+1} = \sum_{n=0}^{\infty}\EulernumberE{n}\frac{t^{n}}{n!}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{2e^{t}}{e^{2t}+1} = \sum_{n=0}^{\infty}\EulernumberE{n}\frac{t^{n}}{n!}</syntaxhighlight> || <math>|t| < \tfrac{1}{2}\pi</math> || <syntaxhighlight lang=mathematica>(2*exp(t))/(exp(2*t)+ 1) = sum(euler(n)*((t)^(n))/(factorial(n)), n = 0..infinity)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[2*Exp[t],Exp[2*t]+ 1] == Sum[EulerE[n]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Missing Macro Error || Successful || - || Successful [Tested: 4]
| [https://dlmf.nist.gov/24.2.E6 24.2.E6] || <math qid="Q7404">\frac{2e^{t}}{e^{2t}+1} = \sum_{n=0}^{\infty}\EulernumberE{n}\frac{t^{n}}{n!}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{2e^{t}}{e^{2t}+1} = \sum_{n=0}^{\infty}\EulernumberE{n}\frac{t^{n}}{n!}</syntaxhighlight> || <math>|t| < \tfrac{1}{2}\pi</math> || <syntaxhighlight lang=mathematica>(2*exp(t))/(exp(2*t)+ 1) = sum(euler(n)*((t)^(n))/(factorial(n)), n = 0..infinity)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[2*Exp[t],Exp[2*t]+ 1] == Sum[EulerE[n]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Missing Macro Error || Successful || - || Successful [Tested: 4]
|-  
|-  
| [https://dlmf.nist.gov/24.2#Ex3 24.2#Ex3] || [[Item:Q7405|<math>\EulernumberE{2n+1} = 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\EulernumberE{2n+1} = 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>euler(2*n + 1) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>EulerE[2*n + 1] == 0</syntaxhighlight> || Missing Macro Error || Failure || - || Successful [Tested: 3]
| [https://dlmf.nist.gov/24.2#Ex3 24.2#Ex3] || <math qid="Q7405">\EulernumberE{2n+1} = 0</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\EulernumberE{2n+1} = 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>euler(2*n + 1) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>EulerE[2*n + 1] == 0</syntaxhighlight> || Missing Macro Error || Failure || - || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/24.2#Ex4 24.2#Ex4] || [[Item:Q7406|<math>(-1)^{n}\EulernumberE{2n} > 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>(-1)^{n}\EulernumberE{2n} > 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>(- 1)^(n)* euler(2*n) > 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>(- 1)^(n)* EulerE[2*n] > 0</syntaxhighlight> || Missing Macro Error || Failure || - || Successful [Tested: 3]
| [https://dlmf.nist.gov/24.2#Ex4 24.2#Ex4] || <math qid="Q7406">(-1)^{n}\EulernumberE{2n} > 0</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>(-1)^{n}\EulernumberE{2n} > 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>(- 1)^(n)* euler(2*n) > 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>(- 1)^(n)* EulerE[2*n] > 0</syntaxhighlight> || Missing Macro Error || Failure || - || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/24.2.E8 24.2.E8] || [[Item:Q7407|<math>\frac{2e^{xt}}{e^{t}+1} = \sum_{n=0}^{\infty}\EulerpolyE{n}@{x}\frac{t^{n}}{n!}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{2e^{xt}}{e^{t}+1} = \sum_{n=0}^{\infty}\EulerpolyE{n}@{x}\frac{t^{n}}{n!}</syntaxhighlight> || <math>|t| < \pi</math> || <syntaxhighlight lang=mathematica>(2*exp(x*t))/(exp(t)+ 1) = sum(euler(n, x)*((t)^(n))/(factorial(n)), n = 0..infinity)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[2*Exp[x*t],Exp[t]+ 1] == Sum[EulerE[n, x]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Failure || Successful || Error || Successful [Tested: 18]
| [https://dlmf.nist.gov/24.2.E8 24.2.E8] || <math qid="Q7407">\frac{2e^{xt}}{e^{t}+1} = \sum_{n=0}^{\infty}\EulerpolyE{n}@{x}\frac{t^{n}}{n!}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{2e^{xt}}{e^{t}+1} = \sum_{n=0}^{\infty}\EulerpolyE{n}@{x}\frac{t^{n}}{n!}</syntaxhighlight> || <math>|t| < \pi</math> || <syntaxhighlight lang=mathematica>(2*exp(x*t))/(exp(t)+ 1) = sum(euler(n, x)*((t)^(n))/(factorial(n)), n = 0..infinity)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[2*Exp[x*t],Exp[t]+ 1] == Sum[EulerE[n, x]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Failure || Successful || Error || Successful [Tested: 18]
|-  
|-  
| [https://dlmf.nist.gov/24.2.E9 24.2.E9] || [[Item:Q7408|<math>\EulernumberE{n} = 2^{n}\EulerpolyE{n}@{\tfrac{1}{2}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\EulernumberE{n} = 2^{n}\EulerpolyE{n}@{\tfrac{1}{2}}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>euler(n) = (2)^(n)* euler(n, (1)/(2))</syntaxhighlight> || <syntaxhighlight lang=mathematica>EulerE[n] == (2)^(n)* EulerE[n, Divide[1,2]]</syntaxhighlight> || Missing Macro Error || Successful || - || Successful [Tested: 3]
| [https://dlmf.nist.gov/24.2.E9 24.2.E9] || <math qid="Q7408">\EulernumberE{n} = 2^{n}\EulerpolyE{n}@{\tfrac{1}{2}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\EulernumberE{n} = 2^{n}\EulerpolyE{n}@{\tfrac{1}{2}}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>euler(n) = (2)^(n)* euler(n, (1)/(2))</syntaxhighlight> || <syntaxhighlight lang=mathematica>EulerE[n] == (2)^(n)* EulerE[n, Divide[1,2]]</syntaxhighlight> || Missing Macro Error || Successful || - || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/24.2.E10 24.2.E10] || [[Item:Q7409|<math>\EulerpolyE{n}@{x} = \sum_{k=0}^{n}{n\choose k}\frac{\EulernumberE{k}}{2^{k}}(x-\tfrac{1}{2})^{n-k}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\EulerpolyE{n}@{x} = \sum_{k=0}^{n}{n\choose k}\frac{\EulernumberE{k}}{2^{k}}(x-\tfrac{1}{2})^{n-k}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>euler(n, x) = sum(binomial(n,k)*(euler(k))/((2)^(k))*(x -(1)/(2))^(n - k), k = 0..n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>EulerE[n, x] == Sum[Binomial[n,k]*Divide[EulerE[k],(2)^(k)]*(x -Divide[1,2])^(n - k), {k, 0, n}, GenerateConditions->None]</syntaxhighlight> || Missing Macro Error || Failure || - || <div class="toccolours mw-collapsible mw-collapsed">Failed [3 / 9]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: Indeterminate
| [https://dlmf.nist.gov/24.2.E10 24.2.E10] || <math qid="Q7409">\EulerpolyE{n}@{x} = \sum_{k=0}^{n}{n\choose k}\frac{\EulernumberE{k}}{2^{k}}(x-\tfrac{1}{2})^{n-k}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\EulerpolyE{n}@{x} = \sum_{k=0}^{n}{n\choose k}\frac{\EulernumberE{k}}{2^{k}}(x-\tfrac{1}{2})^{n-k}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>euler(n, x) = sum(binomial(n,k)*(euler(k))/((2)^(k))*(x -(1)/(2))^(n - k), k = 0..n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>EulerE[n, x] == Sum[Binomial[n,k]*Divide[EulerE[k],(2)^(k)]*(x -Divide[1,2])^(n - k), {k, 0, n}, GenerateConditions->None]</syntaxhighlight> || Missing Macro Error || Failure || - || <div class="toccolours mw-collapsible mw-collapsed">Failed [3 / 9]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: Indeterminate
Test Values: {Rule[n, 1], Rule[x, 0.5]}</syntaxhighlight><br><syntaxhighlight lang=mathematica>Result: Indeterminate
Test Values: {Rule[n, 1], Rule[x, 0.5]}</syntaxhighlight><br><syntaxhighlight lang=mathematica>Result: Indeterminate
Test Values: {Rule[n, 2], Rule[x, 0.5]}</syntaxhighlight><br>... skip entries to safe data</div></div>
Test Values: {Rule[n, 2], Rule[x, 0.5]}</syntaxhighlight><br>... skip entries to safe data</div></div>
|}
|}
</div>
</div>

Latest revision as of 12:01, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
24.2.E1 t e t - 1 = n = 0 B n t n n ! 𝑡 superscript 𝑒 𝑡 1 superscript subscript 𝑛 0 Bernoulli-number-B 𝑛 superscript 𝑡 𝑛 𝑛 {\displaystyle{\displaystyle\frac{t}{e^{t}-1}=\sum_{n=0}^{\infty}B_{n}\frac{t^% {n}}{n!}}}
\frac{t}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullinumberB{n}\frac{t^{n}}{n!}
| t | < 2 π 𝑡 2 𝜋 {\displaystyle{\displaystyle|t|<2\pi}}
(t)/(exp(t)- 1) = sum(bernoulli(n)*((t)^(n))/(factorial(n)), n = 0..infinity)
Divide[t,Exp[t]- 1] == Sum[BernoulliB[n]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]
Failure Successful Successful [Tested: 6] Successful [Tested: 6]
24.2#Ex1 B 2 n + 1 = 0 Bernoulli-number-B 2 𝑛 1 0 {\displaystyle{\displaystyle B_{2n+1}=0}}
\BernoullinumberB{2n+1} = 0

bernoulli(2*n + 1) = 0
BernoulliB[2*n + 1] == 0
Failure Failure Successful [Tested: 3] Successful [Tested: 3]
24.2#Ex2 ( - 1 ) n + 1 B 2 n > 0 superscript 1 𝑛 1 Bernoulli-number-B 2 𝑛 0 {\displaystyle{\displaystyle(-1)^{n+1}B_{2n}>0}}
(-1)^{n+1}\BernoullinumberB{2n} > 0

(- 1)^(n + 1)* bernoulli(2*n) > 0
(- 1)^(n + 1)* BernoulliB[2*n] > 0
Failure Failure Successful [Tested: 1] Successful [Tested: 3]
24.2.E3 t e x t e t - 1 = n = 0 B n ( x ) t n n ! 𝑡 superscript 𝑒 𝑥 𝑡 superscript 𝑒 𝑡 1 superscript subscript 𝑛 0 Bernoulli-polynomial-B 𝑛 𝑥 superscript 𝑡 𝑛 𝑛 {\displaystyle{\displaystyle\frac{te^{xt}}{e^{t}-1}=\sum_{n=0}^{\infty}B_{n}% \left(x\right)\frac{t^{n}}{n!}}}
\frac{te^{xt}}{e^{t}-1} = \sum_{n=0}^{\infty}\BernoullipolyB{n}@{x}\frac{t^{n}}{n!}
| t | < 2 π 𝑡 2 𝜋 {\displaystyle{\displaystyle|t|<2\pi}}
(t*exp(x*t))/(exp(t)- 1) = sum(bernoulli(n, x)*((t)^(n))/(factorial(n)), n = 0..infinity)
Divide[t*Exp[x*t],Exp[t]- 1] == Sum[BernoulliB[n, x]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]
Failure Successful Successful [Tested: 18] Successful [Tested: 18]
24.2.E4 B n = B n ( 0 ) Bernoulli-number-B 𝑛 Bernoulli-polynomial-B 𝑛 0 {\displaystyle{\displaystyle B_{n}=B_{n}\left(0\right)}}
\BernoullinumberB{n} = \BernoullipolyB{n}@{0}

bernoulli(n) = bernoulli(n, 0)
BernoulliB[n] == BernoulliB[n, 0]
Successful Successful - Successful [Tested: 3]
24.2.E5 B n ( x ) = k = 0 n ( n k ) B k x n - k Bernoulli-polynomial-B 𝑛 𝑥 superscript subscript 𝑘 0 𝑛 binomial 𝑛 𝑘 Bernoulli-number-B 𝑘 superscript 𝑥 𝑛 𝑘 {\displaystyle{\displaystyle B_{n}\left(x\right)=\sum_{k=0}^{n}{n\choose k}B_{% k}x^{n-k}}}
\BernoullipolyB{n}@{x} = \sum_{k=0}^{n}{n\choose k}\BernoullinumberB{k}x^{n-k}

bernoulli(n, x) = sum(binomial(n,k)*bernoulli(k)*(x)^(n - k), k = 0..n)
BernoulliB[n, x] == Sum[Binomial[n,k]*BernoulliB[k]*(x)^(n - k), {k, 0, n}, GenerateConditions->None]
Failure Successful Successful [Tested: 9] Successful [Tested: 9]
24.2.E6 2 e t e 2 t + 1 = n = 0 E n t n n ! 2 superscript 𝑒 𝑡 superscript 𝑒 2 𝑡 1 superscript subscript 𝑛 0 Euler-number-E 𝑛 superscript 𝑡 𝑛 𝑛 {\displaystyle{\displaystyle\frac{2e^{t}}{e^{2t}+1}=\sum_{n=0}^{\infty}E_{n}% \frac{t^{n}}{n!}}}
\frac{2e^{t}}{e^{2t}+1} = \sum_{n=0}^{\infty}\EulernumberE{n}\frac{t^{n}}{n!}
| t | < 1 2 π 𝑡 1 2 𝜋 {\displaystyle{\displaystyle|t|<\tfrac{1}{2}\pi}}
(2*exp(t))/(exp(2*t)+ 1) = sum(euler(n)*((t)^(n))/(factorial(n)), n = 0..infinity)
Divide[2*Exp[t],Exp[2*t]+ 1] == Sum[EulerE[n]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]
Missing Macro Error Successful - Successful [Tested: 4]
24.2#Ex3 E 2 n + 1 = 0 Euler-number-E 2 𝑛 1 0 {\displaystyle{\displaystyle E_{2n+1}=0}}
\EulernumberE{2n+1} = 0

euler(2*n + 1) = 0
EulerE[2*n + 1] == 0
Missing Macro Error Failure - Successful [Tested: 3]
24.2#Ex4 ( - 1 ) n E 2 n > 0 superscript 1 𝑛 Euler-number-E 2 𝑛 0 {\displaystyle{\displaystyle(-1)^{n}E_{2n}>0}}
(-1)^{n}\EulernumberE{2n} > 0

(- 1)^(n)* euler(2*n) > 0
(- 1)^(n)* EulerE[2*n] > 0
Missing Macro Error Failure - Successful [Tested: 3]
24.2.E8 2 e x t e t + 1 = n = 0 E n ( x ) t n n ! 2 superscript 𝑒 𝑥 𝑡 superscript 𝑒 𝑡 1 superscript subscript 𝑛 0 Euler-polynomial-E 𝑛 𝑥 superscript 𝑡 𝑛 𝑛 {\displaystyle{\displaystyle\frac{2e^{xt}}{e^{t}+1}=\sum_{n=0}^{\infty}E_{n}% \left(x\right)\frac{t^{n}}{n!}}}
\frac{2e^{xt}}{e^{t}+1} = \sum_{n=0}^{\infty}\EulerpolyE{n}@{x}\frac{t^{n}}{n!}
| t | < π 𝑡 𝜋 {\displaystyle{\displaystyle|t|<\pi}}
(2*exp(x*t))/(exp(t)+ 1) = sum(euler(n, x)*((t)^(n))/(factorial(n)), n = 0..infinity)
Divide[2*Exp[x*t],Exp[t]+ 1] == Sum[EulerE[n, x]*Divide[(t)^(n),(n)!], {n, 0, Infinity}, GenerateConditions->None]
Failure Successful Error Successful [Tested: 18]
24.2.E9 E n = 2 n E n ( 1 2 ) Euler-number-E 𝑛 superscript 2 𝑛 Euler-polynomial-E 𝑛 1 2 {\displaystyle{\displaystyle E_{n}=2^{n}E_{n}\left(\tfrac{1}{2}\right)}}
\EulernumberE{n} = 2^{n}\EulerpolyE{n}@{\tfrac{1}{2}}

euler(n) = (2)^(n)* euler(n, (1)/(2))
EulerE[n] == (2)^(n)* EulerE[n, Divide[1,2]]
Missing Macro Error Successful - Successful [Tested: 3]
24.2.E10 E n ( x ) = k = 0 n ( n k ) E k 2 k ( x - 1 2 ) n - k Euler-polynomial-E 𝑛 𝑥 superscript subscript 𝑘 0 𝑛 binomial 𝑛 𝑘 Euler-number-E 𝑘 superscript 2 𝑘 superscript 𝑥 1 2 𝑛 𝑘 {\displaystyle{\displaystyle E_{n}\left(x\right)=\sum_{k=0}^{n}{n\choose k}% \frac{E_{k}}{2^{k}}(x-\tfrac{1}{2})^{n-k}}}
\EulerpolyE{n}@{x} = \sum_{k=0}^{n}{n\choose k}\frac{\EulernumberE{k}}{2^{k}}(x-\tfrac{1}{2})^{n-k}

euler(n, x) = sum(binomial(n,k)*(euler(k))/((2)^(k))*(x -(1)/(2))^(n - k), k = 0..n)
EulerE[n, x] == Sum[Binomial[n,k]*Divide[EulerE[k],(2)^(k)]*(x -Divide[1,2])^(n - k), {k, 0, n}, GenerateConditions->None]
Missing Macro Error Failure -
Failed [3 / 9]
Result: Indeterminate
Test Values: {Rule[n, 1], Rule[x, 0.5]}

Result: Indeterminate
Test Values: {Rule[n, 2], Rule[x, 0.5]}

... skip entries to safe data